Kualitas Zat Gizi Mikro Dan Sensori Snack Bar Tempo Bagi Penderita Hipertensi - Indra Rukmana; Thresia Dewi Kartini Berek; Sirajuddin Sirajuddin (Media Kesehatan Politeknik Kesehatan Makassar, 2023)
Restricted sodium intake can prevent an increase in blood pressure and increased potassium can lower blood pressure. Porang tubers contain glucomannan which can bind bile salts and stimulate the formation of new bile salts, thus lowering blood pressure. This study aims to determine the quality of micro minerals and sensory snack bar tempo. This research method is pre-experiment with post-test group design. Sodium and potassium levels were analysed by spectrophotometric method. Sensory quality was assessed based on the acceptability test on 30 panellists. Sodium and potassium data were analysed with one-way anova test and sensory quality data were tested with kruskall wallis and if there was a difference, continued with man whitney test. The results showed that the lowest sodium level of tempo snack bar was at 5% concentration of 17.55 mg/100 g and the highest potassium level was at 2.5% concentration of 0.37 mg/100 g of tempo snack bar. The sensory quality of the tempo snack bar from the aspect of the most preferred colour is the concentration of 2.5% (17.5 grams), the aroma aspect is 7.5% (35 grams), the texture aspect is 7.5% (35 grams) and the taste aspect is 7.5% (35 grams) so that the average acceptability of the most preferred tempo snack bar is the concentration of 7.5% (35 grams). The conclusion of this study is that the tempo snack bar that has the best micro-mineral and sensory quality and is acceptable is the 7.5% concentration tempo snack bar. Hypertension patients can consume tempo snack bar as much as 7 pieces (140 g)/day to fulfil the need for snacks.